2020
DOI: 10.1038/s41598-020-74640-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment with the angiotensin receptor 1 blocker losartan protects renal blood flow and oxygen delivery after propofol-induced hypotension in pigs

Abstract: Hypotensive events are strongly correlated to the occurrence of perioperative acute kidney injury, but the underlying mechanisms for this are not completely elucidated. We hypothesised that anaesthesia-induced hypotension causes renal vasoconstriction and decreased oxygen delivery via angiotensin II-mediated renal vasoconstriction. Pigs were anaesthetised, surgically prepared and randomised to vehicle/losartan treatment (0.15 mg*kg−1). A deliberate reduction in arterial blood pressure was caused by infusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…1]. In accordance to our recently published porcine study, losartan infusion had no significant effect on baseline variables (26). Hypotensive hemorrhage caused a transient decrease in urine output in the losartan-treated [À1.5 (CI: 0.7-2.4) mL•min À1 , P = 0.02, Table 1] but not in the vehicle-treated animals (P = 0.30).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…1]. In accordance to our recently published porcine study, losartan infusion had no significant effect on baseline variables (26). Hypotensive hemorrhage caused a transient decrease in urine output in the losartan-treated [À1.5 (CI: 0.7-2.4) mL•min À1 , P = 0.02, Table 1] but not in the vehicle-treated animals (P = 0.30).…”
Section: Resultssupporting
confidence: 85%
“…Renal vascular beds seem more susceptible than the heart, brain and skeletal muscle to ANG II-mediated effects (63). From a renal perspective, the current data and previous reports suggest that ANG II per se might do more harm than is usually acknowledged in susceptible high-risk individuals when exposed to anesthesiaand hemorrhage-induced hypotensive events (26). Congruent with this hypothesis studies have reported that continuing preoperative ANG II inhibition is imperative to reduce postoperative morbidity and mortality (64,65).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…10 If the arterial blood pressure falls below the autoregulatory threshold, RBF is reduced in parallel to the reduction in pressure. 11,12 Even short-term hypotension (1−5 minutes) with mean arterial pressure below 55 mmHg has been associated with increased incidence of postoperative AKI. 9 It remains unclear how RBF and the autoregulatory threshold in humans is affected by anesthesia, but it is likely that major reductions in arterial blood pressure significantly impair RBF.…”
mentioning
confidence: 99%